SUGGESTIONS ON INTRODUCING CLIL IN PRIMARY SCHOOLS - Madaminova Moxlaroyim Rustambek qizi (Journal of new century innovations, 2022)
Abstract – CLIL stands for Content and Language Integrated Learning. It refers to coaching topics such as Science, History or Geography to college students thru a overseas language. This may be accomplished with the aid of using the overseas language trainer the use of pass curricular content material or through the challenge instructor the use of a overseas language because the language of education, or via way of means of each instructors, coaching in tandem. Both techniques bring about the simultaneous mastering of content material and of a overseas language. The gift paper is supposed to assist instructors new to CLIL to begin imposing CLIL sports successfully and come to be snug inside this new method, in addition to assist college students higher adapt to the CLIL technique. The paper turned into organized as a part of Guidelines on a way to useCLIL in number one colleges evolved below the C4C- CLIL for Children European funded Erasmus+ undertaking. Keywords – CLIL, mastering patterns, language, overseas language